Modulation of Superoxide Dismutase 2 Antioxidant Gene Expression by Adjunctive Liquorice Therapy in Periodontitis: A Pilot Randomized Controlled Trial - Akshatha Anand; S Gopalakrishnan; Uma Sudhakar; Manisha Manoj (Journal of Dental Health and Oral Research, 2026)
Introduction: Liquorice (Glycyrrhiza glabra) possesses diverse pharmacological properties, including antimicrobial, anti-inflammatory, antioxidant, hepatoprotective and neuroprotective effects. Superoxide Dismutase 2(SOD2), a key antioxidant enzyme, plays an important role in protecting tissues against oxidative stress and has been extensively studied in periodontitis, where oxidative stress contributes to disease progression. Objective: To assess the efficacy of liquorice as an adjunct to Scaling and Root Planing (SRP) Clinical parameters and Superoxide Dismutase 2(SOD2) levels in periodontitis patients were assessed Methodology: This randomized controlled clinical trial included 40 patients who were randomly allocated into two groups by the coin-toss method: Group 1 (control) and Group 2 (test). All patients received SRP in Group 1 and Group 2 received SRP and liquorice tablet. Clinical parameters like PPD, CAL and GCF samples (SOD2 gene expression) were evaluated at base line and 2 weeks after SRP. Results: Statistically significant improvements in clinical and biochemical parameters were observed in both Groups over time. Conclusion: Adjunctive systemic liquorice therapy may be used as an effective adjunct to SRP for treating periodontitis.